2021
DOI: 10.4018/jgim.2021010105
|View full text |Cite
|
Sign up to set email alerts
|

Price Strategy, Market Orientation, and Business Performance in the Hotel Industry

Abstract: This study seeks to study the relationship between market orientation and business performance and to evaluate the mediating effect of adopting a low-price strategy in this relationship in the hotel industry. A sample from the Spanish and Portuguese hotel industry is used. Results show that the effect of market orientation on business performance is positive and direct. On the other hand, the results do not confirm the mediating effect of a strategy based on low-price in the strength of this relationship. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 83 publications
1
11
0
4
Order By: Relevance
“…According to the study's analyses, MO has a direct positive effect on hotel performance. This finding supports earlier empirical studies on the subject (Campo et al , 2014; Hinson et al , 2017; Kazemian et al , 2021; Otysna and Kamewor, 2022; Sampaio et al , 2019a, b, 2021). Following the definition of MO by Narver and Slater (1990), it is conceivable to assert that MO results in superior customer value, resulting in a continuous increase in business performance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to the study's analyses, MO has a direct positive effect on hotel performance. This finding supports earlier empirical studies on the subject (Campo et al , 2014; Hinson et al , 2017; Kazemian et al , 2021; Otysna and Kamewor, 2022; Sampaio et al , 2019a, b, 2021). Following the definition of MO by Narver and Slater (1990), it is conceivable to assert that MO results in superior customer value, resulting in a continuous increase in business performance.…”
Section: Discussionsupporting
confidence: 91%
“…The connection between MO and hotel performance has been proven in numerous studies. Some research discovered a direct positive association (Campo et al , 2014; Hinson et al , 2017; Kazemian et al , 2021; Otysna and Kamewor, 2022; Sampaio et al , 2019a, b, 2021), while others found no significant effect (Alnawas and Hemsley-Brown, 2019; Phan et al , 2021; Qu, 2014). The most plausible reason for these contradictory outcomes is that MO is insufficient to increase hotel performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common factors influencing users’ switching behavior include quality, satisfaction, value, trust, commitment, price perception, alternative attitudes, social impacts, switching costs, previous switching behavior, and diversification tendencies (Kesharwani et al 2021 ; Li 2021 ; Rahman et al 2020 ; Rouibah et al 2021 ; Sampaio et al 2021 ; Shiau et al 2021 ; ZareRavasan and Krčál 2021 ). Digital currency and electronic payment research focusing on consumers’ choices of payment tools is increasing (Wu et al 2022 ).…”
Section: Theoretical Backgroundsmentioning
confidence: 99%